STUDI TENTANG BUSANA PENGANTIN MELAYU JAMBI DI KECEMATAN KOTA BARU KOTA JAMBI - Sari, Desy Permata; Ramainas, Ramainas; Yuliarma, Yuliarma (Journal of Home Economics and Tourism, 2015)
This study aimed to describe the Jambi Malay wedding dress at New TownDistrict of the city of Jambi, which include 1) Fashion Design and 2) Proceduresfor usage. The method used in this research is descriptive qualitative method. Thetechnique of collecting document through observation, interviews anddocumentation. Instruments in which the researcher's own research. The results ofthe study include the Malay wedding dress design wedding dress Track Menwear, under wear sleeveless shirt, vest and pants made of satin, or velvet santungred, blue or yellow. Gloves made from songket songket red, belt / belt made ofcopper gilt and gold, Keris, slippers. Clothing bride wearing braces satin shirt red,blue or yellow, Songket made songket and red, made from pandanus folding bunhair and pandanus, Flower Flower cempako and shake made from copper gilt goldcolored, flower bunch of white fabric, flower potpourri made from white paper,green, yellow and red, chiffon scarf cinde green and yellow, red satin made Lotus,necklace Tread Jayo and necklace chain, Pending / belt, bracelet canoe, jaggedBracelet, Earrings and Bracelet flat tembago made from gold gilt, Slippers.Decoration on clothing to wear gold thread embroideries, sequins and beads. Theprocedure for starting the use of wear songket, wearing braces, wearing a lotus,papyrus and folding bun wearing a headdress (folding bun pandanus, pesangkon,and puncture bun), wear earrings, wear a necklace, wear pending and scarves,wear bracelets hand, wearing slippers and the men wear trousers, wear depth,songket wear gloves, wear peding and dagger, vest, wear gloves and daggersongket, wear track, wearing slippers.Keywords: Jambi Malay Wedding Dress